Analisis Rasio Keuangan Sebagai Tolak Ukur Peringkat Kinerja Keuangan Studi Kasus PDAM Tirta Pakuan Bogor Periode 2018 – 2022 - Agus Cahyana; Desmy Ariany; Rahayu Putri Utami (Jurnal Syntax Admiration, 2024)
Financial performance is a measure of the effectiveness and efficiency in utilizing the financial resources of an entity to achieve predetermined goals. PDAM Tirta Pakuan Bogor, a regional service company in the city of Bogor, serves as the primary distributor, ensuring the availability of drinking water for the local community. Therefore, financial performance analysis is crucial as a tool for information and joint evaluation for PDAM Tirta Pakuan. The quantitative analysis in this study employs several ratios with the following results: Profitability - Return On Equity (ROE): 9% (Not Good), Return On Asset (ROA): 7% (Not Good). Liquidity - Cash Ratio: 149% (Excellent), Current Ratio: 154% (Excellent). Operating Ratio - Operating Ratio: 154% (Excellent), Operating Profit Margin Ratio: 30% (Less than optimal). Activity Ratio - Receivable Turnover: 85% (Excellent), Bad Debt To Sales: 13% (Not Good). Solvency - Debt To Equity Ratio (DER): 35% (Low), Debt To Assets Ratio (DAR): 27% (Less than optimal). Based on the ratio rating indicators from the BUMD 2020 Performance Book according to Domestic Decision No. 47 of 1999, 2020, the financial performance of PDAM Tirta Pakuan is deemed "Very Good." This analysis provides essential information for PDAM Tirta Pakuan in conducting evaluation and improvements to enhance its financial performance.